Phylactolaemate bryozoans at the Zoological Survey of India and a taxonomic key to Indian Phylactolaemata - Wood, Timothy S. (Zootaxa, 2022)
A review of the phylactolaemate (freshwater) bryozoan collection at the Zoological Survey of India in Kolkata reaches the following conclusions: (1) Fredericella indica Annandale, 1909 from the Indian subcontinent is not the same as the species widely known as F. indica from the northern temperate zones; the latter species name is now changed to Fredericella borealis; (2) Plumatella bigemmis Annandale, 1919 is a junior synonym of Plumatella fungosa Pallas, 1768; (3) Plumatellia persica Annandale, 1919 is a junior synonym of Plumatella casmiana Oka, 1907; (4) Plumatella (Afrindella) testudinicola Annandale, 1912 combines two previously known species: Plumatella bombayensis Annandale, 1908 and Plumatella casmiana Oka, 1907; (5) Rumarcanella minuta (Toriumi, 1941) is a junior synonym of Stolella himalayana Annandale, 1911 which now becomes Rumarcanella himalayana based on statoblast hypertubercles; (6) Plumatella longigemmis Annandale, 1915 and Hyalinella (Australella) indica Annandale, 1915 are both junior synonyms of Hyalinella lendenfeldi (Ridley, 1886); (7) Stolella indica Annandale, 1909, Swarupella andamanensis Rao, 1961 and Swarupella kasetsartensis Wood, 2006, may all be synonymous. The species Plumatella bombayensis is confirmed, and its holotype is re-described. In addition to Fredericella borealis four new species are presented: Plumatella crispa, P. dhritiae, P. paltensis and P. raoi. Validity is rejected for the genera Afrindella, Australella, Stolella, and Swarupella. The genera Rumarcanella and Varunella require refinement and documentation. A taxonomic key to the Indian Phylactolaemata concludes this paper.